MINERALOGY AND PETROLOGY OF THE BRNJICA GRANITOIDS (EASTERN SERBIA) - Vaskovic, N.; Kuroneos, A.; Christofides, G.; Sreckovic-Batocanin, D.; Milovanovic, D. (Bulletin of the Geological Society of Greece, 2004)
The Variscan Brnjica granitoids in East Serbia, occurring in the Kucaj Terrane of the Carpatho-Balkanides, are composed of hornblende - biotite tonalité (TON), biotite granodiorite (GRD), twomica granite (TMG) and leucogranite (LG). The rocks analyzed are slightly peraluminous. A preplate collision tectonic environment is supported based on the R1-R2 discrimination diagram. A two-step mixing plus fractional crystallization (MFC) process is considered responsible for the evolution of the Brnjica granitoids. In the 1st step, the parental magma (having the composition of the more basic TON) is forming the mineral assemblage Pl596Biio.3Hbio.7Mto.7Titi.oQzi7.7 by 44% crystallization, and at the same time is mixed (r=0.1) with a magma similar to TMG to give a melt similar to the composition of the less evolved GRD. In the 2nd step, 60% crystallization (Pl39oKfi oBÌ25oZr06Api aMti 4Titi 0QZ303) of the less evolved GRD and a simultaneous mixing with the same acid magma (TMG) but with higher r (0.6) is needed for the genesis of GRD group. The TON could originate in the crust by melting of amphibolites and basalts under various P-T conditions while the granites could be crustal melts produced by melting of amphibolites, gneisses, graywackes and pelites. Pressure of 2.3 to 4.1 kb and temperatures from 626 to 813 °C were calculated for TON, using hornblende and co-existing hornblende and plagioclase compositions respectively.